Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1038/srep05510
|View full text |Cite
|
Sign up to set email alerts
|

Natural small-molecule enhancers of autophagy induce autophagic cell death in apoptosis-defective cells

Abstract: Resistance of cancer cells to chemotherapy is a significant problem in oncology, and the development of sensitising agents or small-molecules with new mechanisms of action to kill these cells is needed. Autophagy is a cellular process responsible for the turnover of misfolded proteins or damaged organelles, and it also recycles nutrients to maintain energy levels for cell survival. In some apoptosis-resistant cancer cells, autophagy can also enhance the efficacy of anti-cancer drugs through autophagy-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
122
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(127 citation statements)
references
References 56 publications
(81 reference statements)
2
122
0
Order By: Relevance
“…With respect to this interaction, Ajabnoor et al induced paclitaxel resistance in MCF-7 cells at clinically relevant drug doses with profound downregulation of apoptotic molecules and showed progressive mechanistic shift to autophagic death as the principal mechanism of druginduced cytotoxicity [124]. Similarly, naturally occurring alkaloid molecules, including isoliensinine, dauricine, and cepharanthine induce autophagic death in apoptosis-defective cells [125]. In most invasive carcinoma cases, particular molecules like PI3K, Akt, mTOR, NF-B, and MEK/ERK were aberrantly expressed, resulting in apoptotic resistance to various therapeutic approaches Fig.…”
Section: Inducing Autophagic Cell Death In Apoptosis Deficient/resistmentioning
confidence: 99%
“…With respect to this interaction, Ajabnoor et al induced paclitaxel resistance in MCF-7 cells at clinically relevant drug doses with profound downregulation of apoptotic molecules and showed progressive mechanistic shift to autophagic death as the principal mechanism of druginduced cytotoxicity [124]. Similarly, naturally occurring alkaloid molecules, including isoliensinine, dauricine, and cepharanthine induce autophagic death in apoptosis-defective cells [125]. In most invasive carcinoma cases, particular molecules like PI3K, Akt, mTOR, NF-B, and MEK/ERK were aberrantly expressed, resulting in apoptotic resistance to various therapeutic approaches Fig.…”
Section: Inducing Autophagic Cell Death In Apoptosis Deficient/resistmentioning
confidence: 99%
“…14 More recently, natural compounds from alkaloids including liensinine exhibit anticancer effects through the modulation of MTOR-dependent autophagy. 15 However, the exact mechanism by which liensinine regulates autophagy in human breast cancer cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously demonstrated that disorders in autophagy may lead to cancer; this may also be used as a type of anticancer therapy by promoting autophagic cell death in tumors (8). However, since the role of autophagy in cell survival and death remains unclear, further studies are required to determine its function (9).…”
Section: Introductionmentioning
confidence: 99%